Fragmented Justice: How the Wedding Cake Model is Influenced by the 'No Viral, No Justice' Phenomenon - Kadir, Zul Khaidir (International Journal of Law Analytics, 2024)
One relevant model for understanding how the justice system classifies cases is the wedding cake model. However, the existence of social media has presented new challenges. Ironically, viral cases jump over the traditional hierarchy in this model. This study uses a qualitative research method with a conceptual approach. The results of the study show that the phenomenon of "no viral, no justice" creates a situation where the exposure and popularity of a case on social media can shift attention and resource allocation which are basically limited. Meanwhile, the Wedding Cake Model is distorted by public pressure coming from the digital space. Reform of the justice system is needed to maintain objectivity and independence in facing the digital era.